On the ignition of H11B fusion fuel - Ghorbanpour, Esmat; Belloni, Fabio (Frontiers in Physics, 2024)
We have revisited recent results on the ideal ignition of H11B fuel, in the light of the latest available reactivity, an alternative self-consistent calculation of the electron temperature, an increased extent of the suprathermal effects and the impact of plasma density. At high density, we find that the ideal ignition temperature is appreciably relaxed (e.g., Ti≃150 keV for ni∼1026 cm−3 and an optimal 11B/H concentration ε=0.15) and burn becomes substantial. We have then investigated central hot-spot ignition in both isobaric and isochoric inertial confinement configurations. Although implosion-driven ignition appears to be unfeasible, the isochoric self-heating conditions foster favourable preliminary conclusions on the utilization of proton fast ignition. In the isochoric case, we find a broad minimum in the ignition energy at ρR≃8.5 g/cm2 and 220≲Ti≲340 keV (80 ≲Te≲95 keV), for ε=0.15.